Cytokines (IL 1β and IL 6) responses in non-pregnant does infected with corynebacterium pseudotuberculosis following intradermal route of infection in chronic state - Abdullah, Faez Firdaus Jesse; Abdul Latif, Nur-Amirah; Lim, Eric Teik Chung; Adamu, Lawan; Sarah, Siti Aimi; Zamri-Saad, Mohd; Haron, Abdul Wahid; Mohd Lila, Mohd Azmi; Zakaria, Zunita (Pashupati Foundation India, 2016)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis (CLA) which commonly affects sheep and goats. The disease remains as a major disease causing economic loss to the small ruminant industries. There is little information related to responses of interleukin-1β and interleukin-6 in the chronic states. This study was designed to determine the serum concentrations of interleukin-1β and interleukin-6 (pg/mL) in non-pregnant does experimentally inoculated with Corynebacterium pseudotuberculosis via intradermal route in chronic form. Eighteen non-pregnant healthy Katjang does aged 2 years old were divided randomly into two groups. The control and the treatment groups consist of nine does each and were kept for 3 months. The control group was inoculated with PBS solution while the treatment group was inoculated intradermally with C. pseudotuberculosis. Serum samples were collected every 3 days (72 hours) for 3 months (2064 hours). The present study showed significant increase in IL-1β (278 ± 19.19 pg/mL) after 1day (24 hours) of post infection (p<0.0001) which decreased sharply (98.31 ± 19.19 pg/mL) after 5 days (120 hours) of post infection (p = 0.9293) and attained a significant concentration (217.43 ± 19.19 pg/mL) after 3 months (2064 hours) of post infection (p<0.0048) in does challenged with C. pseudotuberculosis compared to the control group. In contrast, the concentration of IL-6 increased significantly (p<0.0001) to (56.43 ± 1.98 pg/mL) in 2 months (1392 hours) of post infection and then decreased significantly (p<0.0001) to concentration of (22.18 ± 1.98 pg/mL) in 3 months (2064 hours) compared to the control group. In conclusion, the present study indicate that the importunity of C. pseudotuberculosis is associated with persistently high concentrations of IL-1β and low concentration of IL-6 which, when interpreted, could severely contribute to pathological vicissitudes and injury of organs and tissues in the chronic stage of C. pseudotuberculosis infections.